Stable thin-shells from 5-dimensional extremal Einstein-Yang-Mills fields - Mazharimousavi, S. Habib; Halilsoy, Mustafa (World Scientific Publ Co Pte Ltd, 2019)
By employing exact Einstein-Yang-Mills (EYM) solution in (4+1) dimensions we establish spherical thin-shells with mass and Yang-Mills charge. Remarkably these shells are stable against linear, radial perturbations with a barotropic fluid presented on the shell with a generic equation of state p = p(sigma) supporting the speed of sound 0 < omega(= partial derivative p/partial derivative sigma) < 1.
Keywords: Einstein-Yang-Mills; higher dimensional black hole; thin-shell; stability